Shepherd on Meaning, Reference, and Perception - David Landy (Journal of Modern Philosophy)
The aim of this paper is to present an interpretation of Shepherd’s account of our most fundamental cognitive powers, most especially the faculty that Shepherd calls perception, which she claims is a unity of contributions from the understanding and the senses. I find that Shepherd is what we would nowadays call a meaning holist: she holds that the meaning of any natural-kind term is constituted by its place in a system of definitions, which system specifies the causal roles of the objects its terms name. Such an account of meaning raises questions about the contact that such a system of definitions, or conceptual scheme, makes with the world. The natural place to seek answers to these questions is in Shepherd’s account of perception, which I argue Shepherd takes to be our most fundamental cognitive faculty. Our cognitive lives begin with perceptions, representations of objects as the cause of those very perceptions of them. With this interpretation in hand, I draw a contrast between it and Boyle’s and Lolordo’s recent work on Shepherd’s theory of meaning. I argue that for Shepherd truths about the causal powers of objects are analytic, and that the relevant empirical questions answered by science concern whether our conceptual scheme accurately represents the world. Finally, I provide additional support for this interpretation by showing that it comports with Shepherd’s criticism of her philosophical opponents, Berkeley, Hume, and Reid.